A comparative and ultrastructural study of synaptic contacts established by primary sensory fibers in the spinal trigeminal nucleus of the rat - Lapa, R. C.R.S.; Bauer, J. A. [UNESP]; Lindsey, C. J. (Elsevier, 1996)
A quantitative evaluation of the types of afferent synaptic contacts in the pars oralis, using transganglionic degeneration and a comparison of previous data obtained from the pars interpolaris of the rat was performed. Following left inferior alveolar nerve transection or partial pulpectomy of the first and second left lower molar teeth well-defined degenerating terminals appeared bilaterally. In both experiments, the majority of these afferent synapses formed single asymmetric contacts with intermediate and distal dendritic segments in the pars oralis. Fewer contacts were observed with dendritic spines, proximal dendritic segments, perikarya, and other terminals. Double and multiple synaptic contacts, preferentially with small dendritic profiles, were also found. Pars oralis showed higher density of degenerating terminals and higher proportion of the contralateral contacts than pars interpolaris suggesting that it is a prime input area and that it may play a role in the bilateral management of sensory information. Pars oralis showed a higher density of contacts with intermediate and distal dendritic segment and a lower density of double contacts in comparison to the pars interpolaris. Partial pulpectomy revealed a distribution in synaptic types similar to that following IAN transection suggesting that sensory fibers conveying pain-related stimuli are not distinguished from fibers of other sensory modalities as to preference of synaptic contacts. The overall pattern demonstrates a structural organization of the sensory inputs to the spinal trigeminal nucleus regarding the bilateral handling of sensory information.
Keywords: Inferior alveolar nerve afferent; Interpolaris; Oralis; Synapses; Tooth pulp afferent; Transganglionic degeneration; Trigeminal